2023
DOI: 10.2196/41861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Clinician Expectations of mHealth Solutions to Increase Rapid-Screening for HIV and Hepatitis in Migrant Populations in France: Qualitative Study

Abstract: Background Migrants underuse screening opportunities for HIV, hepatitis B, and hepatitis C despite elevated risk factors for contracting these infections. Language barriers are an often given as reasons for limiting access to services. Translation and communication apps increase communication and overall patient satisfaction in the patient-provider relationship. In the development and adoption of new technology, expectations play an important role. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Evidence from Western Europe and USA demonstrated that mHealth applications increased screening rate and diagnostic yield for HIV, HBV/HCV among MIDP [68][69][70]. eHealth/mHealth interventions were particularly successful at targeting gay men and other MSM populations, using existing acceptability of online community outreach to boost PrEP uptake and HIV testing services [48].…”
Section: Strategies To Address Sexual Health Challengesmentioning
confidence: 99%
“…Evidence from Western Europe and USA demonstrated that mHealth applications increased screening rate and diagnostic yield for HIV, HBV/HCV among MIDP [68][69][70]. eHealth/mHealth interventions were particularly successful at targeting gay men and other MSM populations, using existing acceptability of online community outreach to boost PrEP uptake and HIV testing services [48].…”
Section: Strategies To Address Sexual Health Challengesmentioning
confidence: 99%